Latecomers. - Savige, Jaya (University of Queensland Press, 2005)
Winner of the prestigious Arts Queensland Thomas Shapcott Poetry Prize, Jaya Savige's Latecomers is a first collection of poems by one of Australia's most exciting young poets. Lively, playful, and always intelligent, Savige's poems show an awareness of place, of the inescapability of history, and a personal commitment to the precision of language.""The poems in Latecomers go beyond what we take for granted these days in a first collection: refinement of language and cadence, allusiveness, wit. Moving easily through abstract wonders and the streets of the inne.